Nutritional interventions for osteoarthritis: targeting the metabolism-inflammation-oxidative stress axis—clinical evidence and translational practice - Wang, Yushan; Cao, Zhiyan; Gao, Yingjie; Shao, Pengfei; Gao, Shuai; Dong, Mingjie; Tian, Zui; Feng, Yi; Xu, Jiake; Xiang, Chuan (Frontiers in Nutrition, 2025)
Osteoarthritis (OA) is the most common chronic joint disease worldwide. Increasing studies have confirmed that obesity, metabolic status and gut microbiota imbalance can promote the occurrence of OA through the “metabolism-inflammation-oxidative stress” network, which is closely related to daily nutrition or dietary intake. The key nutrients with therapeutic effects mainly exert anti-inflammatory, anti-oxidative and chondro-protective effects. Among them, ω-3 polyunsaturated fatty acids and polyphenols are important components of anti-inflammatory diets, while collagen peptides, vitamin D, calcium, probiotics, glucosamine, chondroitin and hyaluronic acid are commonly used in clinical practice as important nutritional support treatments or preventive measures for OA to promote cartilage repair. In terms of dietary patterns, the Mediterranean diet (MD) rich in various nutrients can be used as the basic pattern for OA patients due to its anti-inflammatory and anti-oxidative properties and good clinical effects. Based on MD and evidence from clinical studies, this review constructs a four-level progressive nutritional plan for OA patients with the goals of relieving pain, delaying cartilage degeneration, improving function, and reducing the need for drugs and surgical intervention. We have also proposed customized nutritional management strategies for several special OA populations to reduce the occurrence of nutrition-related adverse events. Collectively, systematic nutritional intervention is expected to become the third major treatment alongside physical and drug therapy, enabling more OA patients to avoid adverse effects caused by repeated drug use and potential risks associated with surgery and prosthesis replacement.